Bohr, Quantum Physics and the Laozi. Issue 3 (3rd July 2017) - Lee, Keekok
ABSTRACT: This contribution argues that Bohr's notion of complementarity can be traced back to the Laozi which he would have read. In Chinese philosophy, polar contrasts such as yin and yang are not regarded as mutually exclusive; they are co-present, existing as a harmonious Whole . Such a conception of metaphysics and logic stood Bohr in good stead for characterising quantum phenomena which are at once both wave and particle. His notion of complementarity bears witness to the possibility of communication and understanding between two different philosophical approaches and scientific traditions—this account adds to Lloyd's concept of semantic stretch.